The Need for Advanced Public Transport Information Services When Making Transfers - Molin, Eric; Chorus, Caspar; Sloten, Ruud van (European Journal of Transport and Infrastructure Research, 2009)
This paper reports on a stated choice experiment examining the determinants of travelers' need and willingness to pay for advanced public transport information services. Specific attention is given to the role of making transfers in the decision to acquire specific types of information. Intercity train travelers are asked to choose among information services that varied in type of information provided by the services, precision of provided dynamic travel time estimates, whether or not the system can provide information unasked for and price. Respondents made these choices conditional on a specified transfer context, denoting whether or not transfers had to be made during the trip, and whether these were transfers to high or low frequency train services. Modeling results indicate that as hypothesized, transferring during the trip, especially towards low frequency connections, induces a larger need for travel information, a higher preference for services that can provide advice relative to other information and a higher willingness to pay for information in general. However, the choice for information services is highly price sensitive, which suggest a low overall willingness to pay.